Assessing the effectiveness of intensive conservation actions: Does guarding and feeding increase productivity and survival of Egyptian Vultures in the Balkans?. (June 2016) - Oppel, Steffen; Dobrev, Vladimir; Arkumarev, Volen; Saravia, Victoria; Bounas, Anastasios; Kret, Elzbieta; Skartsi, Theodora; Velevski, Metodija; Stoychev, Stoycho; Nikolov, Stoyan C.
Abstract: Assessing the effectiveness of conservation measures to reverse population declines is essential to evaluate management strategies. Management solutions such as direct protection or supplementary feeding typically aim at reducing mortality or increasing productivity, but demonstrating such demographic consequences of adopted management is often difficult. Here we assess the effectiveness of large-scale management actions aimed at the conservation of an endangered vulture on the Balkan Peninsula by extending a novel analysis to estimate seasonal adult survival from observations of unmarked individuals. We monitored Egyptian Vulture Neophron percnopterus breeding success and territory occupancy over 11 years in three countries during which both nest guarding and supplementary feeding were carried out. We found little evidence that nest guarding and supplementary feeding increased breeding propensity (mean = 0.88 ± 0.32 standard deviation, n  = 463), breeding success (0.82 ± 0.39), or the number of fledglings raised by successful pairs (1.3 ± 0.74). We estimated adult survival during the 23-week breeding season (mean = 0.936, 95% credible interval 0.889–0.968) and found no significant increase due to management. In the last 13 years 43 dead adult birds have been found during the breeding season, and 77% of confirmed mortalities were due to poisoning. Overall, the current management measures may have so far failed to halt ongoing population declines because the beneficial effects are insufficient to offset the loss of adult birds for example due to poisoning. We suggest that additional measures to slow the decline of Egyptian Vultures in the Balkans are required. In the short term, we urge governments to enforce anti-poison regulations that already exist. In the medium term, alternative approaches need to be developed that reduce the use of poisons and the associated accidental mortality of vultures and other wildlife species.